Customer satisfaction and switching behavior in Islamic banking: evidence from Indonesia - Abduh, Muhamad; Kassim, Salina; Dahari, Zainurin (IIU Press and Research Centre, A.C., 2012)
This study is aimed at investigating the dimensions of customer satisfaction in Indonesia Islamic banking industry and how those dimensions could affect the customers’ switching behavior. Data collection is done by using self administered questionnaire and involves as many as 732 Islamic bank customers from the area of Jakarta. The methods used in this study are factor analysis and logistic regression model. Factor analysis has successfully uncovered the five dimensions of Indonesia Islamic banking customer satisfaction i.e. profitability, bank staff, accessibility, costs, and bank physical appearance. Afterwards, logistic regression evidences that four dimensions are significantly affecting Islamic bank customers’ intention to switch namely bank staff, bank physical appearance, accessibility, and costs. Profitability is perceived less important by respondents with regard to bank-switching issues. Key words: Islamic Banking, Customer Satisfaction, Switching Behavior, Indonesia